Video reportaje / :grupos de danza folklórica del sector La Ronda, en el centro de Quito - Cerón Lechón, Katty Fernanda (2017)
“Ballet Latinoamericano Kallpañan” is an indigenous dance company who undertakes educative projects with an impact on society through artistic-formative programs oriented to awaken attitudes that strengthen their self-esteem, consciously recognize their essence and cultural identity and unwrap as protagonists and actors in the development and progress of its environment.Throughout its career the Ballet Latinoamericano Kallpañan has carried out researches to realize the assembly of its choreographies, among the most important currently presents: Pawkar Raymi, Inti Raymi and Ñuca Llacta. This research sets as a preliminary study for the development of a communicative product whose objective is to make the Ecuadorian ancestral heritage visible through the work carried out by Ballet Latinoamericano Kallpañan. These types of inquiry immersed within the analysis of traditional pop culture as a mechanism to set consecutiveness, offers the country the opportunity to recognize and preserve its identity, history and the values which distinguish it and make it unique. The audiovisual project, outcome of this study, is based on the Organic Law of Communication which promotes the creation of communicative products with a social focus and that make prevail educational and cultural content. The use of the video report as a colophon for the theoretical work, allows to show images, sound, even the facial expressions of the interviewees, considering all this intrinsic information of great importance to understand the project that wields this dance company.